Underappreciated role of canopy nitrogen deposition for forest productivity - Xiaowei Li; Chenlu Zhang; Beibei Zhang; Li Jiang; Shengqi Tang; Chenhui Sun; Yulong Bai; Yubang Wang; Yifei Shi; Lei Ma; Wei Zhang; Qing Ye; et al. (Proceedings of the National Academy of Sciences, 2025)
Atmospheric nitrogen (N) deposition is generally expected to stimulate plant carbon (C) sequestration and promote tree growth, thereby mitigating atmospheric CO 2 accumulation. Yet, the magnitude of N deposition contribution to forest productivity remains contentious. While correlative studies suggest substantial plant growth enhancement, controlled fertilization experiments typically demonstrate a limited impact. This discrepancy may arise from whether or not to consider canopy N uptake processes. Here, we conducted a 10-y field experiment comparing canopy addition of N (CAN) with understory addition of N (UAN) at the rate of 0, 25, and 50 kg N ha –1 y –1 in a temperate deciduous forest in central China. We show that CAN significantly enhanced net primary productivity by 37.0% over control, driven by enhanced leaf litterfall, wood and fine root production, whereas UAN effects were marginal (8%). 15 N isotopic tracing revealed that CAN, through enhanced plant N uptake and increased ecosystem N retention, yielded a 3.5-fold higher C sequestration efficiency (∆C/∆N) of 54.5 ± 7.7 kg C kg –1 N, than UAN (12.2 ± 3.4 kg C kg –1 N) resulted from greater N loss through leaching. Physiological measurements indicated CAN enhanced leaf photosynthetic rates, modified leaf morphology, and extended leaf lifespan via delayed senescence. These findings provide robust empirical evidence that canopy N uptake is crucial for maximizing N-induced forest productivity, thereby holding significant implications for refining global C models and urging modelers to incorporate canopy processes for more accurate projections of future C sinks and climate change mitigation strategies.